Oil problems in Thailand in the past between 1973-1980 - Wisansuwannakorn, Tassaneeporn (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
This academic article It is a study of the causes of oil problems in the past. Born between 1973-1980. During that time, Thailand has experienced two high oil prices in a short period of time. This is mainly due to the role of OPEC in determining the amount of production and setting the price of oil in the world. As a result, Thailand which mainly imports oil from abroad. In addition, oil is an important energy for the country’s economic and industrial activities. The impact of high oil prices has caused widespread trouble for all groups of Thai people. Especially the impact on the lifestyle of Thai people at that time. There was a rally against expensive products. Objection to the increase in bus fare. The call of the people in the society for the government to solve the oil price problem. Including the way of life of Thai people that has changed from complying with the government’s measures to save fuel and electricity. Oil problems during that time. Therefore, it is the first time that Thai people have learned and realized the problem of oil.